Design and Simulation of a Scalable IoT-Based Multi-Sensor Prototype for Pipeline Security Monitoring - Udeh, Evander Chika; Agwu, Michael Chukwuebuka; Akinrinde, Pamilerin Samuel; Ugwuanyi, Nnaemeka Sunday; Nwogu, Akudo Ogechi (PT. Teknologi Futuristik Indonesia, 2026)
Pipeline vandalism and leaks pose a significant threat to global energy infrastructure, leading to severe economic losses and environmental degradation. Traditional surveillance methods are often reactive and insufficient for monitoring vast, remote pipe-line networks in real-time. To address this gap, this study designs and simulates a multi-sensor Internet of Things (IoT) proto-type that integrates gas, vibration, and temperature monitoring for anomaly detection. The methodology employs a design-and-simulation approach using an Arduino Uno and ESP8266 Wi-Fi module within the Proteus environment. Key findings demonstrate the functional correctness of the system’s logic, achieving consistent alert triggering based on predefined heuristic thresholds with no failures in the simulated environment. These results imply that a low-cost, multi-modal sensor fusion approach provides a technically feasible foundation for future physical deployment in infrastructure security.